2018
DOI: 10.1002/pmic.201700250
|View full text |Cite
|
Sign up to set email alerts
|

Specific T Cell Responses against Minor Histocompatibility Antigens Cannot Generally Be Explained by Absence of Their Allelic Counterparts on the Cell Surface

Abstract: Allogeneic stem cell transplantation has emerged as immunotherapy in the treatment of a variety of hematological malignancies. Its efficacy depends on induction of graft versus leukemia by donor lymphocytes. Both graft versus leukemia and graft versus host disease are induced by T cells reactive against polymorphic peptides, called minor histocompatibility antigens (MiHA), which differ between patient and donor and are presented in the context of self-HLA (where HLA is human leukocyte antigen). The allelic cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
(34 reference statements)
0
13
0
3
Order By: Relevance
“…For known MiHAs, the independent discovery of two variants of the same MiHA is very unlikely as only a small number of MiHAs have been discovered and the systematic investigation of counterpart peptide immunogenicity is usually not performed. Recent quantitative MS experiments, focused on specific MiHAs rather than the whole immunopeptidome, confirmed that some MiHAs, previously thought to be dominant, were actually co-dominant ( 47 ). If the MiHA co-dominant/dominant ratio suggested by in silico analysis is valid, approximately half of the MiHAs would be categorized as co-dominant and the number of targetable antigens would substantially increase.…”
Section: Resultsmentioning
confidence: 88%
“…For known MiHAs, the independent discovery of two variants of the same MiHA is very unlikely as only a small number of MiHAs have been discovered and the systematic investigation of counterpart peptide immunogenicity is usually not performed. Recent quantitative MS experiments, focused on specific MiHAs rather than the whole immunopeptidome, confirmed that some MiHAs, previously thought to be dominant, were actually co-dominant ( 47 ). If the MiHA co-dominant/dominant ratio suggested by in silico analysis is valid, approximately half of the MiHAs would be categorized as co-dominant and the number of targetable antigens would substantially increase.…”
Section: Resultsmentioning
confidence: 88%
“…Absolute quantification of pMHCs to date is most commonly performed by comparing endogenous levels of pMHCs to exogenous peptide standards, again failing to account for sample losses [21][22][23][24] . Losses can be accounted for with internal pMHC standards, but require laborious refolding of pMHCs for every target of interest 19,25 . Nevertheless, this approach relies on single point calibration, ignoring the effects of ion suppression, thereby inaccurately estimating absolute pMHC levels in quantitative analyses.…”
mentioning
confidence: 99%
“…For some MiHAs both alleles encode MHC-presented peptides, potentially making them immunogenic in both directions (co-dominant). In this case, T-cells discriminate peptides by a single amino acid difference (10). Up to date over 60 MiHAs have been discovered.…”
Section: Introductionmentioning
confidence: 99%